MEMBANGUN APLIKASI PEMBUATAN SURAT KETERANGAN KULIAH, SURAT PENGANTAR PENELITIAN DAN PENGAJUAN CUTI BERBASIS WEB - COMPUTING INFORMATIKA; Iyus A Muslimin (COMPUTING | Jurnal Informatika, 2021)
Making lecture certificates, research cover letters and submitting leave that still uses the manual method, namely offline at the Administration of the Faculty of Information Technology, University of Bale Bandung where students go directly to Administration to submit the required letters, then the letters submitted on that day are not always completed on the same day. The purpose of this research is to develop applications for making lecture certificates, research cover letters and web-based leave applications and to facilitate Administration and Students in processing data such as making lecture certificates, research cover letters and submitting leave. The methodology used is the agile method in its stages, namely planning, system analysis, design, implementation, system testing. The features of this application consist of filling out forms for students, in addition to students, other features for admin are viewing letters, printing letters, viewing KRS and proof of payment, as well as the whatsapp feature for contacting students. Based on the results of analysis, design, testing using the black-box testing method, it was found that the application for Making Lecture Certificates, Research Cover Letters, and Web-Based Leave Applications that can be accessed directly by students and Administrative Staff as efficiency in processing data in making letters required by students during the study period